2017
DOI: 10.1002/cpmb.34
|View full text |Cite
|
Sign up to set email alerts
|

Direct Isolation of Seamless Mutant Bacterial Artificial Chromosomes

Abstract: Seamless (i.e., without unwanted DNA sequences) mutant bacterial artificial chromosomes (BACs) generated via recombination-mediated genetic engineering (recombineering) are better suited to study gene function compared to complementary DNA (cDNA) because they contain only the specific mutation and provide all the regulatory sequences required for in vivo gene expression. However, precisely mutated BACs are typically rare (∼1:1,000 to 1:100,000), making their isolation quite challenging. Although these BACs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 24 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…7 With proper primer design, the application of colony PCR can be extended to the analysis of other types of DNA structure changes, even in mixes mostly composed of cells with background DNA structure. 6,8 Here, we successfully applied colony PCR for rapid identification of DGR background cells and downstream mutant DNA structure analysis by DNA sequencing of colony PCR products. Besides, we showed that PCR engineering of DNA termini through using long bipartite primers as well as long range PCR can be implemented in colony PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 With proper primer design, the application of colony PCR can be extended to the analysis of other types of DNA structure changes, even in mixes mostly composed of cells with background DNA structure. 6,8 Here, we successfully applied colony PCR for rapid identification of DGR background cells and downstream mutant DNA structure analysis by DNA sequencing of colony PCR products. Besides, we showed that PCR engineering of DNA termini through using long bipartite primers as well as long range PCR can be implemented in colony PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Electro-competent cells were prepared as described previously. 6 The use of PCR for the introduction of a gap into wild-type Tnnt2 PAC construct and DGR with ssODNs has been described previously. 10 Linear PCR derived DNA was electroporated at 12 000-13 000 V/cm at a time constant of 10 ms, covalently closed circular DNA was electroporated at 17 000-18 000 V/cm at a time constant of 7.5 ms using BioRad Gene Pulser Xcell into 10 μL of electrocompetent cells.…”
Section: Dna Engineeringmentioning
confidence: 99%
“…Electro-competent cells were prepared as described previously 6 . DNA was electroporated at 17,000-18,000 V/cm at time constant 7.5 msec using BioRad Gene Pulser Xcell into 10 μl competent cells.…”
Section: Bacterial Transformationmentioning
confidence: 99%
“…After denaturing DNA was precipitated with EtOH and washed with 70% EtOH, the DNA pellet was dissolved in electroporation buffer 6…”
Section: Bacterial Transformationmentioning
confidence: 99%
See 1 more Smart Citation